2013
DOI: 10.1038/bjc.2013.486
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of bone morphogenetic protein receptor IA in pancreatic cancer is associated with a poor prognosis

Abstract: Background:The expression of SMAD4, the central component of the transforming growth factor-β (TGF-β) and bone morphogenetic protein (BMP) signalling pathways, is lost in 50% of pancreatic cancers and is associated with a poor survival. Although the TGF-β pathway has been extensively studied and characterised in pancreatic cancer, there is very limited data on BMP signalling, a well-known tumour-suppressor pathway. BMP signalling can be lost not only at the level of SMAD4 but also at the level of BMP receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 30 publications
(36 reference statements)
4
23
0
Order By: Relevance
“…Intensity of BMP signaling appears to positively correlate with the degree of cancer malignancy and clinical stage in cancer patients (Helms et al 2005;Alarmo et al 2008;Choi et al 2012;Voorneveld et al 2013). BMP signals differentially modulate the initiation and progression of CRC depending on the Smad4 and p53 status (Voorneveld et al 2015).…”
Section: Tumor Promotion By Bmp Signalsmentioning
confidence: 99%
“…Intensity of BMP signaling appears to positively correlate with the degree of cancer malignancy and clinical stage in cancer patients (Helms et al 2005;Alarmo et al 2008;Choi et al 2012;Voorneveld et al 2013). BMP signals differentially modulate the initiation and progression of CRC depending on the Smad4 and p53 status (Voorneveld et al 2015).…”
Section: Tumor Promotion By Bmp Signalsmentioning
confidence: 99%
“…Any disagreement was resolved by discussion. As shown in Table 1, studies by Voorneveld et al [82], Toga et al [83], Tascilar et al [84], and Singh et al [85] all concluded that PC patients with SMAD4 expression had significantly longer survival as compared to those lacking SMAD4 expression. However, the prognostic difference did not reach statistical significance despite a little improved survival was observed in the studies of Hua et al [86] and Khorana et al [87].…”
Section: Smad4 In Pc Prognosismentioning
confidence: 98%
“…Inactivation of SMAD4 is also associated with poor clinical prognosis, and restoration of SMAD4 in SMAD4-depleted cancer cell lines reduced cell growth [69–71]. In SMAD4-positive pancreatic ductal adenocarcinoma (PDAC), reduction in BMPR1A (ALK3) expression increased cell viability, Matrigel invasion, activation of angiogenesis markers and matrix modification [72]. Treatment with BMP2 decreased the viability of SMAD4-positive PDAC cells, but, paradoxically, increased the viability of SMAD4-negative cells.…”
Section: Role Of Bmp Signalling In Cancer Pathogenesismentioning
confidence: 99%
“…Conversely, treatment with LDN-193189 increased viability of SMAD4-positive cells but decreased viability of SMAD4-negative cells. Together, these results suggest that BMPs have divergent roles in pancreatic cancer pathogenesis depending on the presence or absence of SMAD4: when SMAD4 is present, BMP acts as a tumour suppressor; whereas in its absence, BMP becomes a tumour promoter [72]. Thus, small molecule BMP inhibitors may be selectively therapeutic for SMAD4-negative pancreatic cancer.…”
Section: Role Of Bmp Signalling In Cancer Pathogenesismentioning
confidence: 99%